2015
DOI: 10.1539/joh.14-0117-oa
|View full text |Cite
|
Sign up to set email alerts
|

Influence of illness and unhealthy behavior on health‐related early retirement in Korea: Results from a longitudinal study in Korea

Abstract: sion, diabetes, malignancy, arthritis, cardiovascular and cerebrovascular diseases, smoking, and obesity increased the risk of ERdHP. To enhance the sustainability of labor in an aging society, more studies on ERdHP are needed. (J Occup Health 2015; 57: 28-38) Key words: Aging, Cox proportional hazard model, Early retirement, Gender, Korean longitudinal data Involuntary early retirement is a serious financial concern for workers and their families 1) . Beyond the individual level, early retirement contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…The development of those diseases can have deleterious effects on remaining in paid labor. These results are support Kang et al [18], who suggested that workers with hypertension, diabetes mellitus, malignancy, cardiovascular disease, cerebrovascular disease, and arthritis were more likely to experience IHR.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The development of those diseases can have deleterious effects on remaining in paid labor. These results are support Kang et al [18], who suggested that workers with hypertension, diabetes mellitus, malignancy, cardiovascular disease, cerebrovascular disease, and arthritis were more likely to experience IHR.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis shows that viral hepatitis, ischemic heart disease, congestive heart failure, cerebral stroke, alcoholism, insomnia, urolithiasis, pneumoconiosis, and vertigo strongly increase IHR risk (S1 Table). Part of the associations between specific diseases and IHR which we found in this study are also discussed in previous studies [18, 21]. In addition, we found that some diseases with high prevalence in Asia can be much heavier disease burden to IHR in Asian societies than Western countries (i.e., viral hepatitis, retinal disease et al).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In previous studies, many factors influencing exit from the labor market have been identified. These factors include demographic predictors like age and gender as well as behavioral and lifestyle risk predictors such as physical inactivity and smoking, socioeconomic status, chronic diseases, welfare arrangements, working conditions, and so on. As Schultz proposed, these factors can be seen as “push” and “pull” factors .…”
Section: Introductionmentioning
confidence: 99%